Humeral torsional side differences after nonoperative treatment of proximal humerus fractures and humeral shaft fractures: clinical and ultrasonographic assessment - Sam Razaeian; Jan-Niklas Menzel; Dafang Zhang; Christian Krettek; Nael Hawi (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background The purposes of this study were to investigate (1) sonographic humeral torsion (SHT) and side differences (∆SHT), and (2) to determine the relationship between SHT and range of rotational motion (RORM) as well as functional outcome scores of nonoperatively treated proximal humerus fractures (PHF) and humeral shaft fractures (HSF). Methods Between October 2020 and July 2021, consecutive patients with radiographically healed nonoperatively treated PHF and HSF were included in this analysis. Subjective perception of torsional side difference, correlation between SHT and RORM, Subjective Shoulder Value as well as absolute and adjusted Constant Score were determined. Degree of humeral torsional side differences were classified as follows: 0°–15°: minor; > 15°–30°: moderate; > 30°: major. Factors including gender, hand dominance, fracture type, and displacement were also assessed in order to investigate any association between these variables and ∆SHT. Results Sixty-five patients with nonoperatively treated PHF (n = 47) and HSF (n = 18) were analyzed. Mean follow-up was 13.2 months (range, 2.1–72.6). The majority (80% (52)) resulted in only minor, 15.4% (10) in moderate, and 4.6% (3) in major torsional side differences. Patients with minor or moderate torsional differences did not perceive any subjective side difference. While RORM correlated fairly to highly with functional outcomes, only very low to low correlation was observed between these measures and SHT and ∆SHT. Gender, fracture displacement, and type of fracture were not related to SHT and ∆SHT. However, significantly greater torsional side differences were observed, when the dominant side was involved (p = 0.026). Conclusion Nonoperative early functional treatment of proximal humerus and humeral shaft fractures results mainly in only minor humeral torsional side differences. Minor and moderate amounts of torsional side differences might not be perceived by patients.